THE INFLUENCE OF LEADERSHIP, TEACHER CONFIDENCE, AND MOTIVATION ON TEACHER PERFORMANCE AND STUDENT ACHIEVEMENT IN AN EDUCATIONAL CONTEXT - Putri, Indah Atmaja; Mutiara, Trisna; Ningsih, Vera Yulitiya; Hidayati, Rts. Kholifah; Manik, Monica Angelica (Indonesian Educational Administration and Leadership Journal (IDEAL), 2020)
This research aims to investigate the influence of leadership, teacher self-confidence, and teacher motivation on teacher performance and student achievement in the context of education. This study uses a quantitative approach, and data is collected through surveys and interviews. The research sample consists of teachers and students in various schools in a particular area. The data analysis results indicate that effective leadership has a positive impact on teacher motivation, teacher self-confidence, and teacher performance. Furthermore, teacher motivation also has a positive influence on teacher performance and student achievement. The findings of this research provide important recommendations for the development of leadership and teacher motivation to improve teacher performance and student achievement in the context of education. Keywords: leadership, teacher self-confidence, teacher motivation, teacher performance, student achievement, education